Transações com partes relacionadas sob a ótica da propriedade piramidal - Flores, Silvia Amélia Mendonça (2020)
In the context of concentrated structures, shareholders acquire power due to excess of control rights, compared to their cash flow rights (ownership). The difference between control and ownership is called deviation, common in pyramidal structures. In the pyramidal ownership, the controlling shareholder exercises control through at least one publicly traded company. The business ties established may facilitate the attainment of private benefits, through related party transactions, because the use of these transactions may generate conflicts of interest. Due to these aspects, this research aims to analyze the influence of the deviations of rights from the indirect structure in the related party transactions (RPTs) of companies with pyramidal structures in Brazil. The data were obtained on the Reference Form (document with a wide range of financial, operational, and non-operational information for the organization) for the period from 2010 to 2017, combining OLS panel data and quantile regressions. The deviation between control and ownership was calculated using two methodologies exposed in the literature. In characterizing RPTs, social networking techniques were used, demonstrating that financial transactions, such as interbank deposits and mutual contracts, predominate. In addition, some communities of companies were identified, which establish relationships based on a common controlling shareholder. As for the quantitative analysis, it was observed that the deviations of rights positively influence the total value of related party transactions. This influence was also observed for specific transactions between controlling and/or controlled companies. Regarding the analysis of the influence on the company’s performance and value, it was found that there is an inverse relationship between the value of transactions and performance, represented by the return on assets (ROA). For the firm's value, in most models, there was no statistical significance. Another pertinent contribution refers to corporate governance, which showed a positive relationship with the RPTs. In companies with a pyramidal structure, corporate governance did not exercise the role of moderation in expropriation channels.